2016
DOI: 10.1007/s00167-016-4038-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in anteroposterior stability and proprioception after different types of knee arthroplasty

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 47 publications
4
33
0
Order By: Relevance
“…In addition, BCR TKA knees did not demonstrate increased anteroposterior laxity when compared with the contralateral non‐operated knee ( p = 0.957), consistent with the findings of Camilla et al, using the same BCR TKA implant in a recent in‐vitro study . This finding supports the importance of ACL preservation in restoring anteroposterior stability in previous in‐vitro, in‐vivo, and clinical unicompartmental knee arthroplasty studies . The clinical laxity test may provide a suitable surrogate test for in‐vivo ACL elongation and serve as a potential patient screening tool for consideration of BCR TKA implants.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, BCR TKA knees did not demonstrate increased anteroposterior laxity when compared with the contralateral non‐operated knee ( p = 0.957), consistent with the findings of Camilla et al, using the same BCR TKA implant in a recent in‐vitro study . This finding supports the importance of ACL preservation in restoring anteroposterior stability in previous in‐vitro, in‐vivo, and clinical unicompartmental knee arthroplasty studies . The clinical laxity test may provide a suitable surrogate test for in‐vivo ACL elongation and serve as a potential patient screening tool for consideration of BCR TKA implants.…”
Section: Discussionsupporting
confidence: 86%
“…22,[32][33][34] Wautier and Thienpont compared anteroposterior translation in groups of 10 patients, each with a different type of arthroplasty, including an MS design, two PS designs, and a unicompartmental arthroplasty (UKA) design. 23 They found that the MS design had sagittal plane laxity similar to the UKA, whereas the PS designs had increased laxity at both 30-and 90-degree of knee flexion. They found no differences in patient-reported outcomes including the Knee Society Score and the Forgotten Joint Score.…”
Section: Discussionmentioning
confidence: 97%
“…21,22 Thirty pounds of anterior translation force was applied to the tibia and the anterior displacement was measured in millimeters, as has been previously described. [21][22][23][24][25] The KT-1000 leg positioners were used, and a goniometer was used to confirm appropriate knee flexion prior to testing. Total relaxation of the limb was reinforced throughout the duration of testing, and measurements were repeated until identical measurements (AE0.5 mm) were obtained on three consecutive trials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypermobility, i.e., excessive anterior-posterior (A-P) displacement (Fantozzi et al, 2006;Stoddard et al, 2013) and/or internal-external (I-E) rotation (Wautier and Thienpont, 2017;Zaffagnini et al, 2014) is a familiar manifest of the unbounded kinematic response of an unstable knee. Yet, whether the diagnosis of instability should be excluded when hypermobility is not observed during clinical assessments is a matter of debate (Martín-Hernández et al, 2014;Nakahara et al, 2015).…”
Section: Introductionmentioning
confidence: 99%